Relationships between Mindsets and Weight Control Specific Compensatory Beliefs - ทองวร สิทธิชัย (Journal of the Psychiatric Association of Thailand, 2019)
Objectives : To develop the “Mindset Scale” and investigate relationships between mindsets and weight control specific compensatory beliefs among undergraduate students. Methods : The participants in this study were 654 undergraduate students who were under weight control. The “Mindset Scale” and the “Weight Control Specific Compensatory Scale” were main measurements in this study. Internal consistency was analyzed by Cronbach’s alpha coefficient. In addition, confirmatory factor analysis and structural equation modeling analysis were used to analyze construct validity and relationships between mindsets and weight control specific compensatory beliefs. Results : The “Mindset Scale” consisted of two domains (growth mindset and fixed mindset) and had good internal consistency (Cronbach’s alpha coefficient were between 0.821 - 0.963). Moreover, the growth mindset had negative effect on weight control specific compensatory beliefs and fixed mindset had positive effect on weight control specific compensatory beliefs. Conclusion : The “Mindset Scale” had good psychometric properties which can be applied for further researches. Moreover, mindsets were considered as one of the most important psychological structures which determine individuals’ compensatory beliefs.